The United States and the Second World War : new perspectives on diplomacy, war, and the home front - Piehler, G. Kurt; Pash, Sidney (World War II - the global, human, and ethical dimension, 2010)
Roosevelt at the Rubicon : the great convoy debate of 1941 / J. Garry Clifford and Robert H. Ferrell -- Containment, rollback, and the onset of the Pacific War, 1933-1941 / Sidney Pash -- "In terms of peoples rather than nations" : World War II propaganda and conceptions of U.S. foreign policy / Justin Hart -- Allotment Annies and other wayward wives : wartime concerns about female disloyalty and the problem of the returned veteran / Ann Pfau -- General George S. Patton and the war-winning Sherman tank myth / Nicholas D. Molnar -- Naval gunfire support in Operation Neptune : a reexamination / Barbara Brooks Tomblin -- Veterans tell their stories and why historians and others listened / G. Kurt Piehler -- Semper paratus : the U.S. Coast Guard's Flotilla 10 at Omaha Beach / Mark A. Snell -- American pacifism, the "greatest generation," and World War II / Scott H. Bennett -- Foreign policy experts as service intellectuals : the American Institute of Pacific Relations, the Council on Foreign Relations, and planning the occupation of Japan during World War II / Yutaka Sasaki -- Hiroshima and the U.S. peace movement : commemoration of August 6, 1948-1960 / Rieko Asai